2021
DOI: 10.24839/2325-7342.jn26.2.82
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Religious Attendance, Private Prayer, Religious Coping, Social Support, and Caregiver Burden in Dementia Caregivers

Abstract: Living longer increases the risk of cognitive decline, which can cause individuals to become dependent on caregivers. Due to the stressful nature of caregiving, caregiver burden often negatively impacts the quality of life of caregivers and can even cause premature death. In the present study, we examined the relationships between caregiver burden and social support, religious coping, religious attendance, and participation in private prayer. We hypothesized that each variable would contribute uniquely to care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Past literature has shown the positive implications of social support on the mental and physical wellbeing of support seekers (e.g., Cohen & Syme, 1985;Uchino, 2008). For example, emotional and instrumental support from family can significantly reduce caregiver burden, which has been linked to severe health issues (Mashinchi et al, 2021). Some studies have also suggested that social support is effective in aiding recovery from disease, adaptation to chronic illness, and degree of psychiatric disturbance (Cohen & McKay, 2020;Uchino, 2008).…”
Section: Social Supportmentioning
confidence: 99%
“…Past literature has shown the positive implications of social support on the mental and physical wellbeing of support seekers (e.g., Cohen & Syme, 1985;Uchino, 2008). For example, emotional and instrumental support from family can significantly reduce caregiver burden, which has been linked to severe health issues (Mashinchi et al, 2021). Some studies have also suggested that social support is effective in aiding recovery from disease, adaptation to chronic illness, and degree of psychiatric disturbance (Cohen & McKay, 2020;Uchino, 2008).…”
Section: Social Supportmentioning
confidence: 99%